Evaluation of the effects of three designs of oxygenators with integrated filters on clinical and haematological outcomes at an Australasian cardiothoracic unit. (July 2023) - Prakash, Minesh; Sharma, Varun; Oh, Timothy; Lo, Casey; Parkinson, Grant; McCormack, David; Conaglen, Paul; Lin, Zaw; Kejriwal, Nand; Meikle, Felicity; Peplow, Emma; Bhana, Jack; et al.
Introduction: Cardiopulmonary bypass (CPB) machines have oxygenators with integrated filters and unique biocompatible coatings to combat systemic inflammatory response syndrome (SIRS) and mitigate coagulopathy. Contemporary oxygenators have undergone comparative studies; however, our study aimed to identify the most appropriate oxygenator for our regional Cardiothoracic unit in Australasia. Methods: A prospective audit consecutively recruited one-hundred and fifty patients undergoing cardiac surgery at Waikato Hospital, New Zealand between the periods of 29th January 2018 and 31st July 2018. Fifty patients were recruited for each oxygenator arm: Sorin INSPIRE' (Group-S); Terumo CAPIOX'FX (Group-T); and Medtronic Affinity Fusion' (Group-M). The clinical outcomes were transfusions, chest drain output, reoperation and length of hospital stay (LOHS). Routine blood testing protocol included: haemoglobin, protein, albumin, white cell count (WCC), C-reactive protein (CRP), platelet count and coagulations tests including international normalized ratio (INR). Results: Comparing Groups S, T and M there was no statistical difference in chest drain output (650 vs. 500 vs. 595 ml respectively, p = 0.45), transfusions (61 vs. 117 vs. 70 units, p = 0.67), reoperation (6 vs. 8 vs. 12%, p = 0.99) and LOHS (median 7.4 vs. 7.6 vs. 9.5 days, p = 0.42). Group-T had fewer SIRS cases but similar increase in CRP ( p = 0.12) and WCC ( p = 0.35). Group-M had a significant rise in post-op INR ( p = 0.005) but no associated increase in chest drain output ( p = 0.62). Group-S and -M required more 4%-albumin and Group-T had more transfusions. Only fresh frozen plasma (FFP) and red blood cell (RBC) transfusion had a significant relationship with LOHS ( p < 0.05). Conclusion: Biochemically, there was slight difference among the oxygenators which did not translate into clinical difference in outcomes. The oxygenator design and perfusionist choice aided in our decision-making process.